La délinquance : observatoire méconnu des recompositions des relations villes-campagnes - Jorick Perrin (EchoGéo)
Delinquency’s spatial characteristics, although present in the politico-media speech, remain marginally studied by the French geographers, on the opposite of the Anglo-Saxon geography. However, the transformations at work in the French territories, under the action of the metropolization, affect these spatial characteristics of the delinquency as well as its representations. The statistical mapping and the limits of its application, give way to various interpretations, analyses and communication of the criminal phenomena from the geographical point of view. Contrary to the multiple instrumentalizations of insecurity, delinquency appears, from the geographical point of view, like an observatory making it possible to analyze urban influence on rural and suburban territories. This paper offers some elements to read and analyze the various aspects of this phenomenon, based on a compared statistical analysis and cartography of the delinquency in the police and gendarmerie areas.